RESEARCH ON LOAD TEST AND SPECTRUM COMPILATION METHOD OF LOADER CONNECTING ROD - WAN YiPin; SONG XuDing; CHEN LeLe; ZHANG Lei (Jixie qiangdu)
In order to study the load test and load spectrum for fatigue reliability test of loader connecting rod, a method of connecting rod load test and load spectrum is presented. A kind of sensor is designed to measure the force of the connecting rod. The test experiment was carried out in primary stone, clay, sand and small stone under the conditions of these 4 kinds of material. By using the method of peak valley extraction and wavelet processing, the compression of the measured data is realized. By means of rain flow counting, the relationship between the mean frequency and amplitude frequency of the connecting rod load is obtained under the condition of synthesis, and they are subject to the normal distribution and three parameter Weibull distributions, and the load distribution of the mean value and amplitude distribution are independent of each other. The two-dimensional load spectrum and fatigue test program spectrum of the connecting rod are established, which can provide the basis for the reliability test and anti fatigue design of connecting rod structure.